Cercariae (Digenea: Strigeidae, Diplostomidae) in Biomphalaria straminea (Planorbidae) from a rice field in Northeastern Argentina - Fernández, María Virginia (2017)
The rice fields can provide habitats for many species of aquatic invertebrates, as insects, molluscs, crustaceans; and vertebrates, as fish, amphibians, reptiles and birds, which may act as hosts in the life cycles of digenean parasites. In this context, the goal of the present study was to describe the cercariae found in Biomphalaria straminea from a rice field in Northeastern Argentina. This freshwater snail inhabits a wide variety of environments, favoring shallow, temporary and standing or slow-flowing freshwater bodies. For this study, snails were collected from the cultivated parcels and irrigated channels during the flooding periods (from the time of sowing to soon after harvesting of the rice) between December 2010 and May 2011 and December 2011 and April 2012, in a rice field from Corrientes province, one of the main rice producers of Argentina. A total of 5 510 snails were examined of which 26 were infected with three different larval trematodes belonging to Strigeidae, Furcocercaria V (0.40 %) and Furcocercaria XX (0.04 %), and Diplostomidae, Furcocercaria XIX (0.04 %). Furcocercaria XX and Furcocercaria XIX were present in one rice cultivation cycle, while Furcocercaria V was present in both rice cultivation cycles. The prevalence of the different furcocercariae was somewhat higher in the second rice cultivation cycle. The cercariae described are new records for Argentina that added to 53 cercariae previously reported for Biomphalaria spp. in different aquatic environments of country. The study of the digenean larval in rice fields is important because contribute to the knowledge of the biodiversity of these environments.